Penetapan Dan Prosedur Pembayaran Pajak Kendaraan Bermotor Pada UPPD SAMSAT Surakarta - Puput Kurniawati; Rusnandari Retno Cahyani (Universitas Sahid Surakarta, 2023)
Regulation of the Governor of Central Java No.40 of 2008 concerning the Organization and Work Procedures of the Technical Implementation Unit at the Central Java Provincial Revenue and Regional Asset Management Office, UPPD (Regional Tax Service Unit). SAMSAT Surakarta is a One-Stop Single Administration System, from government agencies in Central Java and surrounding areas. Taxpayers must go through several counters when certifying the STNK. The counters that must be passed by taxpayers include the formular collection counter, the payment and determination counter, the payment and submission counter, and the STNK submission counter. Sometimes this system is difficult for taxpayers who pay vehicle tax for the first time to understand. This research uses interviews and internships at the local UPPD. Tax determination and tax payment are in accordance with applicable procedures and laws and regulations. The process of determining taxes goes well and accordingly but in the process of paying taxes there are still deficiencies but the samsat continues to improve and make improvements in service for the better